Students Perceptions towards Distance Learning with Online Collaborative Platforms: A Case Study - Rukmi, Nala Sita (English Department, Universitas Negeri Surabaya, 2021)
In view of the COVID-19 pandemic and government policy to carry out distance education by employing full online learning. The research explores the EFL students perception toward distance education during Covid19 Pandemic with online collaborative platforms which employed in EFL Students of English Department of a private college in Indonesia. This research used a descriptive case research using purposive sampling techniques by taking 27 respondents from English Department at STKIP PGRI Jombang. The online questionnaire used to collect data on the perception of students by employing online collaborative platforms. The questionnaire are adapted from the technology acceptance model (TAM) constructed by Davis, 1989 with little modification as it excludes the external factors such as the availability of the internet access, and the support from the administration. TAM is possibly the most widely-used framework for measuring technology acceptance, and its high validity has been proven empirically in many previous studies (Basri & Paramma, 2019 and Wiyaka et.al., 2018). The quantitative data was collected using an online questionnaire posted in Google form. The method of descriptive case research in terms of percentage has been used for data processing. The result of this research indicates the positive perception those EFL students of English Department at STKIP PGRI Jombang who took Critical Reading by using online collaborative platforms held on the use of online collaborative platforms. Further research can refer to this Acceptance Model in determining a suitable ICT integrated learning program betien various platform and the user expectations of the online platforms used.